Pharmacoeconomic Model Of Dengue Vaccine In Malaysia - Tay, Chai Jian (2018)
Around two billion people are vulnerable to dengue infections in tropical and subtropical regions, where about 50 to 100 million dengue infections occur each year, leading to 20000 to 30000 deaths annually. Dengue is a mosquito-borne viral disease that is transmitted to humans through the bites of female mosquitoes carrying the virus. Control of dengue epidemic has been elusive, mainly because of the failure to control mosquito breeding habitats in urban environments. Safe, efficacious and cost-effective dengue vaccine is still under testing. The model that links the virus transmission dynamics between mosquito and human is the key to a transparent valuation of dengue vaccine pricing.